SPIRITUALITAS KRISTEN DALAM MATIUS 22:37-40 SEBAGAI POLA HIDUP KRISTIANI - Sibarani, Yosua (Shift Key : Jurnal Teologi dan Pelayanan, 2020)
There are so many questions and personal struggles about the spirituality of a Christian. In practice, spirituality is separated from the reality of life; the higher a person's spirituality, the further he should be from secular life. However, in Christianity, spirituality has a much more special and unique meaning than other religions or beliefs. The Bible has given teachings about true spirituality for believers as written in Matthew 22: 37-40. This article aims to explain the correct meaning of Christian spirituality in Matthew 22: 37-40 as a Christian lifestyle